An Analysis of Air Contamination & Its Impact on Fitness (International Journal of Innovative Research in Computer Science & Technology, 2022)
Many epidemiologic studies throughout  globe have repeatedly shown negative affect of air  contamination on humanoid fitnessiness, & it has  estimated that more than 7 million public die each year as  consequence of air contamination .. Furthermore to  deprived air quality, re is growing evidence that interior air  contamination is a significant danger to humanoid  fitnessiness, particularly in lower-income nations where  biomass fuels are still used as an energy source. When  concentration of certain chemicals in atmosphere exceeds  a specific level, air contamination occurs, which is  detrimental to ecological system as well as normal  circumstances of human life & growth. Scholars have  undertaken a considerable amount of relevant study in face  of increasingly severe environmental contamination  issues, & air contamination forecasting has of vital  significance in those studies. As preventive measure, air  contamination forecasting is foundation aimed at implementing effective contamination management  measures, & precised air contamination predicting has  become a critical job. This review covers what is currently  known about air contamination in low-income  communities.
Keywords: Air contamination; climate; Fitness; Organic compounds; World Fitness Organization (WHO)